Chameleon! - Cowley, Joy.; Bishop, Nic, 1955- (New York : Scholastic Press, 2005)
Experience close-up the many moods (and colors) of chameleons. One brave chameleon ventures from the safety of his tree in search of a new home. On his journey, he meets other rain forest animals, not all of them friendly! Alas, the new tree he chooses is already home to another chameleon. She dons her aggressive coloring until she's sure that the visitor is friend, not foe. Then they welcome each other with brilliant, happy colors. Incredible photographs and simple text perfect for young children is rounded out with informative backmatter on one of the planet's most captivating creatures.
Originally published as: Chameleon, Chameleon.
Keywords: Chameleons -- Juvenile literature; Chameleons